2004
DOI: 10.1108/03090560410539285
|View full text |Cite
|
Sign up to set email alerts
|

Negative symbolic consumption and consumers’ drive for self‐esteem

Abstract: Self-esteem is an important motivational drive for consumption involving both the acceptance and rejection/avoidance of symbolic goods. This paper examines the relationship between self-esteem and the rejection of goods and brands within the context of fashion consumption by young professionals. A conceptualisation which accounts for consumers' use of various strategies in their efforts to maintain or enhance their self-esteem is suggested. A small-scale exploratory study is used to examine first, how consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(252 citation statements)
references
References 43 publications
12
230
1
9
Order By: Relevance
“…It also shows how the clothing was used as a form of camouflage. The results are consistent with Rudd and Lennon (2000), Cash (1990), Fisher (1973 and Boultwood and Jerrard (2000) and Banister and Hogg (2004), who together have indicated that clothing is used as a body image management tool, and also consistent with Kwon and Parham (1994), and Compton (1962), clothing was also used to help strengthen self and body-image perceptions and therefore mood.…”
Section: Body Imagesupporting
confidence: 75%
See 2 more Smart Citations
“…It also shows how the clothing was used as a form of camouflage. The results are consistent with Rudd and Lennon (2000), Cash (1990), Fisher (1973 and Boultwood and Jerrard (2000) and Banister and Hogg (2004), who together have indicated that clothing is used as a body image management tool, and also consistent with Kwon and Parham (1994), and Compton (1962), clothing was also used to help strengthen self and body-image perceptions and therefore mood.…”
Section: Body Imagesupporting
confidence: 75%
“…To summarise, they and Sweeney and Zionts (1989) suggest that clothing serves three purposes: to enhance self-concept, to make us feel good about ourselves, and to make favourable impressions on others. Furthermore, products but in this case clothing, can be seen to be a symbol of individuality and uniqueness, autonomy and importance, affiliation and social identification, all needed for the maintenance and enhancement of self-esteem (Banister & Hogg, 2004). Fashion gives an impression of greater sociability and has shown to lead to closer interpersonal distances; Wearing out of date clothing has shown to induce spatial avoidance reactions for sociability (Workman, 1987).…”
Section: Social Interaction and Clothing/fashionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviour that is compliant with the personal norm enhances self-esteem (Minton & Rose, 1997). Selfesteem is an important motivational drive for a range of consumption behaviours, including acceptance or avoidance of symbolic goods that serve as symbols of either uniqueness or group affiliation (Banister & Hogg, 2004). Some research shows mavens demonstrate relatively high levels of self-esteem (Clark & Goldsmith, 2005).…”
Section: Psychological Factorsmentioning
confidence: 99%
“…The branding strategies are the important part of any marketing plan because it is one of the essential marketing tools to enhance the customer base. The marketers and manufacturers of smartphone should truly emphasis and focus on branding strategies and marketing campaign to make a strong brand and to achieve true customer loyalty and gain a higher market share in their industry.Though, correspondingly effective is the indication which certain persons evade some goods plus products due to undesirable implications/suggestions [15][16][17][18]. However, pending newly [19], this emerging idea is prevailing and getting attention those customers refusing definite products to evade addition rejected implication.…”
mentioning
confidence: 99%